Application of Cox’s Proportional Hazard Model and Construction of Life Table for Under-Five - Shantikumar, Salam Singh (International Journal of Statistics in Medical Research, 2014)
A primary data of 836 eligible women in the age group of 15-49 years is used to determine the causal effects of covariates on under-five mortality. The eight covariates viz., number of family members (NHM), type of toilet facility (TTF), total children ever born (TCB), parity (PAR), duration of breastfeeding (DBF), use contraceptive (CMT), DPT and ideal number of girl (ING) are considered as covariates of the study. By applying Cox’s regression analysis, six covariates viz., TTF, NHM, CMT, DBF, DPT and ING have substantially and significantly effect on under-five mortality. Further, a life table of under-five children under study is constructed using the estimate of survival function obtained from Cox’s regression model.